2014
DOI: 10.1371/journal.pone.0093530
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in UBA3 Confer Resistance to the NEDD8-Activating Enzyme Inhibitor MLN4924 in Human Leukemic Cells

Abstract: The NEDD8-activating enzyme (NAE) initiates neddylation, the cascade of post-translational NEDD8 conjugation onto target proteins. MLN4924, a selective NAE inhibitor, has displayed preclinical anti-tumor activity in vitro and in vivo, and promising clinical activity has been reported in patients with refractory hematologic malignancies. Here, we sought to understand the mechanisms of resistance to MLN4924. K562 and U937 leukemia cells were exposed over a 6 month period to MLN4924 and populations of resistant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…In tumour cell lines and xenografts, treatment-emerging resistance was observed for MLN4924. Sequencing in the resistant lines identified heterologous mutations in UBA3 (predominantly A171T) within the MgATP-binding cleft where MLN4924 also binds (Milhollen et al 2012, Toth et al 2012, Xu et al 2014. These data strongly suggest that the observed biological effects in MLN4924-treated cells are primarily due to NAE inhibition.…”
Section: Development Of Nedd8 Inhibitors-mln4924mentioning
confidence: 80%
See 1 more Smart Citation
“…In tumour cell lines and xenografts, treatment-emerging resistance was observed for MLN4924. Sequencing in the resistant lines identified heterologous mutations in UBA3 (predominantly A171T) within the MgATP-binding cleft where MLN4924 also binds (Milhollen et al 2012, Toth et al 2012, Xu et al 2014. These data strongly suggest that the observed biological effects in MLN4924-treated cells are primarily due to NAE inhibition.…”
Section: Development Of Nedd8 Inhibitors-mln4924mentioning
confidence: 80%
“…Common issues for compounds that enter into clinical trials include the potential development of resistance and their use as single agents or in combination therapy. The studies in tissue culture and xenograft model systems have indeed showed that resistance to MLN4924 is a highly anticipated outcome (Milhollen et al 2012, Toth et al 2012, Xu et al 2014. These results are critical as not only demonstrate that the observed anti-tumour effects of MLN4924 depend primarily on its target, NAE, but also raise the necessity to develop new compounds that potentially will overcome resistance.…”
Section: Potential Strategies For the Use Of Nedd8 Inhibitors In Cancmentioning
confidence: 99%
“…While MLN4924 has been intensively investigated in preclinical and clinical trials, the induction of drug-resistant mutations in UBA3, the molecular target of MLN4924, raises the necessity to identify other therapeutic targets against neddylation pathway [[31], [32], [33]]. In this study, we found that UBC12 was overexpressed in human lung cancer, increased with disease deterioration, and positively correlated with NEDD8 expression.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, other mechanisms of resistance to pevonedistat, which were not explored in this paper but should be considered particularly for cases of acquired resistance, include mutations in components of the neddylation machinery such as UBA3 (i.e. catalytic subunit of NAE) [44, 45]. …”
Section: Discussionmentioning
confidence: 99%